Work-Life Balance, Kepuasan Kerja, Dan Kinerja: Peran Moderasi Family Supportive Supervisor Behaviors - Putri, Firlita Nuriska; Muafi, Muafi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2025)
Students who study while working have to balance their personal life, career, and studies. This research tests and analyzes the relationship between work-life balance, job satisfaction, and performance, moderated by Family Supportive Supervisor Behaviors. The method used in this research is quantitative method by distributing questionnaires to respondents. The sample of this research is 150 undergraduate students who study while working in the Special Region of Yogyakarta. Data analysis in this study used a Structural Equation Model (SEM) using Partial Least Square (PLS). The results of this study indicate that work-life balance has a significant positive effect on job satisfaction and student performance. Job satisfaction is also proven to have a significant positive effect on student performance. However, job satisfaction is proven not to mediate the effect of work-life balance on student performance. In addition, Family Supportive Supervisor Behaviors proved not to strengthen the influence of work-life balance on student performance.